DIGITAL LITERACY AND STUDENT ACADEMIC PERFORMANCE IN UNIVERSITIES: A META-ANALYSIS - Ocvita Ardhiani; M. Noor Rochman Hadjam; Dinda Rakhma Fitriani (Universitas Pendidikan Ganesha, 2023)
The development of Information and Communication Technology in the world, especially the internet, demands its use in the field of Education, in this case students at the university level are required to use blended learning methods so that they must have the skills and skills to use digital technology or digital literacy skills in lectures to support good academic performance. Previous research has shown a correlation between digital literacy and academic performance, but no research has focused on how much influence the r and size of the correlation of the two special variables have on students at the university level. This meta-analysis aims to measure the relationship between digital literacy and student academic performance at the university level by considering the effect size. The total sample in this study was 4105 students from 15 studies that were considered eligible. The results of the meta-analysis show that digital literacy has a positive and significant correlation to student academic performance at the moderate level with a 95% CI (0.184; 0.444). The heterogeneity test showed good results and there was no publication bias.